RESÍDUOS BIOLÓGICOS NOS INSTITUTOS DE MEDICINA LEGAL DE GOIÁS: IMPLICAÇÕES PARA OS TRABALHADORES - BARROS, Izildinha Pedreira (2006)
Institutes of Forensic Medicine (IFM) perform exams and forensic studies implying in the generation of biological, chemical, radioactive, and common wastes. Thus, the workers can be exposed to biohazardous materials, mainly, due to the non-adherence to recommended practices in their management. Aiming at decreasing such risks, the Health Ministry has established rules defining guidelines to be undertaken by all institutions which generate Health Hazardous Wastes (HHW), including Institutes of Forensic Medicine. This paper had the following goals: diagnosing the management of biological waste generated by IFMs in Goiás as well as their implications to the workers; identifying them, in accordance with different stages as established in the current national legislation; verifying the situation of occupational biohazards for the workers of such institutions in Goiás. Data was collected through questionnaires, check lists, and interviews. Questionnaires were applied to 10 directors, and 81 workers were interviewed. The observation outcomes were recorded in a check list. Despite the fact that such facilities generate wastes similarly to any other health care facility, the first ones are non-segregated, non-conditioned and disposed in accordance with current legal rules. Sharp instruments management is shown as a main hazard to workers, which can be evidenced by the records of percutaneous injuries, while discarding. However, there is some awareness among workers concerning biohazards involved in the activities they perform. There is low adherence to protective measures. Most workers do not use protective individual barriers as recommended, and do not show a complete vaccination plan against tetanus and Hepatites B virus. The outcomes show the lack of a policy towards biohazards, and the need of continuing education concerning biosafety measures in such facilities.